Practice and Human Form - Psarros, Nikolaos (Conatus - Journal of Philosophy, 2019)
All variants of pragmatism share the flaw that their concepts of practice rely on the idea of the local value of actions with respect only to locally defined aims and not on the criterion of a universal goodness. This paper claims that such a criterion can be found with the aid of an ontologically founded theory of the Good, which regards forms not as solely noematic universals, but as real, though abstract, entities. The idea of goodness is derived from the thesis of the immediate knowledge of the Good. Further consequences of this form of theoretical foundation of goodness are the abandonment of the dogma of the immediate reference of language to the world as well as of the dogma of the primacy of acting over thinking.